Desarrollo de una aplicación web y móvil para la comercialización de los productos de la mega distribuidora San Juan de la ciudad de Latacunga. - Tituchina Quillupangui, Oscar Enrique (2021)
This technological proposal was made in the Mega Distribuidora "San Juan" which is dedicated to the sale of food in general, for the population of the province of Cotopaxi, Barrio San Juan, where it presents difficulties in its sales activities which They have been carried out through spreadsheets and sale and purchase registration cards, this process generates disorder among the workers who have to go to the different areas to verify the information obtained from the daily sales, in order to plan and carry out the deliveries of the different products. In this sense, the present research work develops a web and mobile application that allows the improvement of the sales process of the products offered by the company, making the sales flow more efficient. For the development of the web application the SCRUM methodology was used, in the development of the mobile application the MOBIL-D methodology was used and the use of open code, a development environment, MySQL database manager and Android Studio, to achieve the automation of sales processes, generating a control of the inputs and outputs of the products, keeping an adequate record of the day's sales, substantially improving the customer service time at each point of sale. Thus producing a significant reduction in customer service hours and reducing customer service costs for the direct benefit of Mega Distribuidora "San Juan".